2009
DOI: 10.5551/jat.2394
|View full text |Cite
|
Sign up to set email alerts
|

RhoA and Rac1 Changes in the Atherosclerotic Lesions of WHHLMI Rabbits

Abstract: Aim:The activation of RhoA and Rac1 is crucial for the pathogenesis of atherosclerosis. This study investigated the changes of unprocessed and mature forms of RhoA and Rac1 in the progression of atherosclerosis. Methods: Unprocessed and geranylgeranylated forms of RhoA and Rac1 in aortic atherosclerotic lesions were separated by the Triton X-114 partition method using Watanabe heritable hyperlipidemic (WHHLMI) rabbits prone to myocardial infarction. The activation of RhoA and Rac1 was determined by membrane tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…John reported that Rac1 participates in LPS activation of TLR4 expression [36]. In the carotid artery injury model, Ohkawara [37] reported that Rac1 activity is higher in atherosclerosis plaques, and is proportional to the degree of hardening of the arteries. Inhibition of Rac1 can inhibit VSMC proliferation induced by PDGF [38] and EGF [39].…”
Section: Discussionmentioning
confidence: 99%
“…John reported that Rac1 participates in LPS activation of TLR4 expression [36]. In the carotid artery injury model, Ohkawara [37] reported that Rac1 activity is higher in atherosclerosis plaques, and is proportional to the degree of hardening of the arteries. Inhibition of Rac1 can inhibit VSMC proliferation induced by PDGF [38] and EGF [39].…”
Section: Discussionmentioning
confidence: 99%
“…B) RAC1. As RhoA, Rac1 expression and activity is increased in arteries from atherogenic animal models (196,255,351). Interestingly, Rac1 expression and activity are reduced by estrogen in vascular smooth muscle and monocytes, suggesting that this effect could participate in the atheroprotective action of estrogen (255).…”
Section: Rho Proteinsmentioning
confidence: 92%
“…RhoA expression and activity increase with cellular infiltration during the progression of atherosclerotic lesions (351). Downstream RhoA, Rho-kinases have been also shown to be upregulated at inflammatory arteriosclerotic lesions in both a porcine model of coronary artery spasm (211) and arteriosclerotic human arteries (212).…”
Section: Rho Proteinsmentioning
confidence: 99%
“…Rac1 is ubiquitously expressed in many cell types, and regulation is both dynamic and contextual. Previous studies have described Rac1 dysregulation as a contributing factor in an array of different pathologies including cardiovascular disease and cancer [1–4] . Dysregulation of Rac1 in endothelial cells (ECs) may be important in disease initiation and progression during cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%